Assessing the effect of extreme weather on population health using consumer-grade wearables in rural Burkina Faso: observational panel study - Koch, Mara; Matzke, Ina; Huhn, Sophie; Sié, Ali; Boudo, Valentin; Compaoré, Guillaume; Maggioni, Martina Anna; Bunker, Aditi; Bärnighausen, Till; Dambach, Peter; Barteit, Sandra (JMIR mhealth and uhealth, 2023)
Background: Extreme weather, including heat and extreme rainfall, is projected to increase owing to climate change, which can have adverse impacts on human health. In particular, rural populations in sub-Saharan Africa are at risk because of a high burden of climate-sensitive diseases and low adaptive capacities. However, there is a lack of data on the regions that are anticipated to be most exposed to climate change. Improved public health surveillance is essential for better decision-making and health prioritization and to identify risk groups and suitable adaptation measures. Digital technologies such as consumer-grade wearable devices (wearables) may generate objective measurements to guide data-driven decision-making.
Gesehen am 31.01.2024